Shape memory effect of PMMA - Ge, Yuchen. (2013)
In order to design thin skin with programmable folding and unfolding configuration under stimuli, material with shape change and memory effect under various stimuli is studied. Among them, Poly methyl methacrylate (PMMA) is a commercial shape memory material. Research projects were first aimed at folding/unfolding effect of thin PMMA specimen with thermal treatment and chemical stimuli.